2000
DOI: 10.1080/00288233.2000.9513447
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of two closes of prostaglandin Fanalogue, Prosolvin, for oestrous synchronisation of Syrian Awassi ewes

Abstract: An assessment was made of the effectiveness of two doses of Prosolvin, a synthetic prostaglandin F2 a , on oestrous synchronisation in local ewes during the breeding season. Thirty cycling Awassi ewes were divided equally into three groups. Ewes in group T10 and group T15 were injected intramuscularly twice with either 10 tng (T10) or 15 mg (T15) of Prosolvin, with an interval of 11 days. The third group received no treatment and served as a control group (C). Oestrus commenced in the ewes in group T10 at 83.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Laparoscopic examination was performed to assess the ovaries and the status of the ovarian response to the hormonal treatments inside and outside the breeding season. This reported work has helped to elucidate some other reproductive parameters in Syrian Awassi ewes as a continuation to previous studies (Zarkawi et al 1999;Zarkawi 2000Zarkawi , 2004.…”
Section: Resultssupporting
confidence: 67%
“…Laparoscopic examination was performed to assess the ovaries and the status of the ovarian response to the hormonal treatments inside and outside the breeding season. This reported work has helped to elucidate some other reproductive parameters in Syrian Awassi ewes as a continuation to previous studies (Zarkawi et al 1999;Zarkawi 2000Zarkawi , 2004.…”
Section: Resultssupporting
confidence: 67%
“…As well Safranski et al (1992) reported that pregnancy period in control ewes and ewes treated with melengestrol acetate + PG-600 was 163.8 and 157.2 days, respectively. In contrast, Zarkawi (2000) reported that the treatment had no effect on the duration of pregnancy, which averaged 150.3 days in control and 150.4, and 150.8 days in synchronized groups with 10mg and 15mg PGF 2 α, respectively. This difference can be likely due to the different breed of sheep and the environment.…”
Section: Gestation Periodmentioning
confidence: 89%
“…Administration of exogenous prostaglandin F 2α (PGF 2α ) during the breeding season induces regression of the corpus luteum (CL), reduces progesterone concentrations, and allows for a new follicular wave to start within 2-3 days (Boland et al 1978). Responses to PGF 2α can be improved by preceding treatment with a 5-day progesterone pessary or gonadotropin releasing hormone (GnRH) or two injections of PGF 2α 11 days apart (Beck et al 1996;Zarkawi 2000;Godfrey et al 2001). However, the 5-day GnRH-PGF 2α programme alone is not effective in oestrus induction of Awassi ewes outside the normal breeding season without progesterone pretreatment (Husein & Kridli 2003).…”
Section: Introductionmentioning
confidence: 99%